Livro dos homens: intertextualidade e vozes narrativas - Braga, Grégore Silva (2013)
The present research workingComparative Literatureturnedto the analysisand interpretation oftalesLivro dos Homens(2005), by RonaldoCorreiade Brito. In the first chapter, we established acorrelationbetween theintertextualnarrative discourseand thebiblical text. Still in thefirst chapter, we sought toexamine, fromtheBakhtinian conceptofcarnivalization, the proceduresof representationof religious cultureof the Brazilian Northeast. In the second chapter, the research focusedon identifying andforms of representationof the voicesthat collaboratewith the narratorin the developmentof narrative discourse. The final conclusionof the workled us tothe conclusion thatRonaldoCorreiade Britois,besideArianoSuassuna, the most importantwriter of theMovimentoArmorial which aimed torealize theartistic and literaryrepresentationofsocial and cultural realityof the Brazilian Northeast.